The Impact of Trust and Platform Innovation on Consumer Behavior in Social Commerce Among Indonesian University Students - Ita Minarni; Jamaluddin; Syahribulan (Journal of Business and Behavioural Entrepreneurship, 2024)
The rapid development of information technology has significantly transformed various aspects of life, including shopping behaviors. Social commerce (s-commerce) has emerged as a fast-growing trend in e-commerce, leveraging social interactions and user contributions to facilitate online transactions. This study aims to investigate the impact of consumer trust and platform innovation on consumer behavior in s-commerce among Indonesian university students. A survey was conducted with 300 students who actively use s-commerce platforms such as Shopee, Tokopedia, and Bukalapak. The data were analyzed using SPSS to examine the relationships between trust, platform innovation, and purchasing behavior. The findings reveal a strong positive correlation between consumer trust and purchasing behavior (r = 0.70), as well as between platform innovation and purchasing behavior (r = 0.60). Furthermore, multiple regression analysis shows that both consumer trust (B = 0.40, p < 0.001) and platform innovation (B = 0.30, p < 0.001) significantly influence purchasing behavior. These results underscore the importance of building consumer trust and continuously innovating platform features to enhance user experience and drive transactions. This study provides valuable insights for s-commerce platforms to develop effective marketing strategies and improve consumer engagement. The implications of this research highlight the need for trust-building measures and innovative platform designs to foster consumer loyalty and increase purchase intentions among university students in Indonesia.